Study of the physico-chemical composition, emission sources and effects on human health of atmospheric aerosols in rural and urban areas in tropical africa - (:unkn) unknown (My University, 2017)
This thesis was a contribution to the INDAAF (International Deposition Network to study and Atmospheric chemistry in Africa) program. It aims was to study the physics and chemistry of atmospheric aerosol collected on two undisturbed African rural sites, representative of forest (Nsimi site Cameroon) and humid savanna (Djougou site Benin) ecosystems. Aerosols collected weekly in the PM2.5 and PM10 fractions at Nsimi, from 2004 to 2009 and at Djougou, from 2005 to 2009 were analyzed in order to characterize the seasonal variations of concentrations of the different chemical species and to identify their major sources according to the seasons. The contribution of each group of species was estimated from the total concentration of the aerosol. The results obtained allowed (1) to highlight the impact of climatic parameters on the concentration levels of the chemical species, with the dry season having the most important impact in general, (2) to identify biomass combustion sources and biofuel, terrigenous, biogenic, secondary as well as predominant in the dry season and biogenic sources, domestic fires and guttation phenomenon in the wet season, (3) to show the impact of the ecosystem and the location on emissions of aerosols: biogenic source and guttation are higher in the forest while terrigenous source is higher in wet savanna. The second part of my thesis is a part of the program POLCA (POLlution African Capitals). The main objective was to characterize particulate pollution in Yaounde, capital of Cameroon, and to study its toxicological impact on the human respiratory system. This work allowed to chemically characterize on a seasonal basis aerosols collected monthly from December 2012 to July 2013 and identify the sources. Furthermore, various tests on biological responses of human epithelial cells exposed to Yaounde aerosols were used to determine their toxicity in humans based on the component chemical species. The results showed (1) the impact of th
Keywords: African Research